16.7 W 885 nm diode-side-pumped actively Q-switched Nd:YAG/YVO4 intracavity Raman laser at 1176 nm. (26th October 2017) - Jiang, Pengbo; Zhang, Guizhong; Liu, Jian; Ding, Xin; Sheng, Quan; Yu, Xuanyi; Sun, Bing; Shi, Rui; Wu, Liang; Wang, Rui; Yao, Jianquan
Abstract: We proposed and experimentally demonstrated the generation of high-power 1176 nm Stokes wave by frequency shifting of a 885 nm diode-side-pumped Nd:YAG laser using a YVO4 crystal in a Z -shaped cavity configuration. Employing the 885 nm diode-side-pumped scheme and the Z -shaped cavity, for the first time to our knowledge, we realized the thermal management effectively, achieving excellent 1176 nm Stokes wave consequently. With an incident pump power of ~190.0 W, a maximum average output power of 16.7 W was obtained at the pulse repetition frequency of 10 kHz. The pulse duration and spectrum linewidth of the Stokes wave at the maximum output power were 20.3 ns and ~0.08 nm, respectively.